FRI0128 A NOVEL FORMULATION OF CT-P13 (INFLIXIMAB BIOSIMILAR) FOR SUBCUTANEOUS ADMINISTRATION: 1-YEAR RESULTS FROM A PART 1 OF PHASE I/III RANDOMIZED CONTROLLED TRIAL IN PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS. (June 2019) - Yoo, DaeHyun; Jaworski, Janusz; Matyska-Piekarska, Ewa; Smiyan, Svitlana; Ivanova, Delina; Zielinska, Agnieszka; Raussi, Eve-Kai; Batalov, Anastas; Lee, Sangjoon; Suh, Jeehye; Han, Noori; Westhovens, Rene
Abstract : Background: Efficacy and safety of a new subcutaneous (SC) formulation (CT-P13 SC) up to Week 30 were comparable with intravenous (IV) formulation (CT-P13 IV) in both patients with rheumatoid arthritis (RA) [1] and Crohn's disease [2]. Objectives: This report is to further investigate pharmacokinetics, efficacy and overall safety of CT-P13 SC in patients with RA throughout the 1-year treatment period. Methods: Patients with active RA (presence of 6 or more swollen and tender joints [of 28 assessed], and serum C-reactive protein [CRP] concentration >0.6 mg/dL) were treated with CT-P13 IV at Weeks 0 and 2, and were randomized for continuation with CT-P13 IV or SC administration at Week 6. The IV cohort received CT-P13 IV 3 mg/kg every 8 weeks and the SC cohorts received CT-P13 SC 90 mg, 120 mg or 180 mg, respectively, every 2 weeks up to Week 54. Pharmacokinetics blood samples were collected before study drug administration at each visit and drug levels were determined by electrochemiluminescent assay. Efficacy parameters including DAS28 and ACR criteria and overall safety were evaluated. Results: A total of 50 patients were enrolled, of whom 48 patients were randomly assigned at Week 6 into 4 cohorts (1:1:1:1 ratio). The mean Ctrough (pre-dose serum concentration of CT-P13 before next dose injection) of SC cohorts throughout the study visits were higher than those of IV cohort after randomization at Week 6. Ctrough levels increased with SC dose and were sufficiently higher than the target therapeutic concentration (1 μg/mL) throughout the study period (Figure 1). Overall, the efficacy results of CT-P13 SC up to Week 54 were comparable to those of CT-P13 IV. Disease improvement by DAS28 (CRP) and ACR20 were comparable across all 4 cohorts, regardless of the route of administration or dosage of CT-P13 (Table 1). The safety profiles which occurred after study drug administration at Week 6 in SC cohorts were generally comparable to those of IV cohort and appeared similar to those previously reported for IV infliximab [3]. All injection site reactions were grade 1 or 2. No malignancy or death was reported (Table 1). Conclusion: The results from 1-year treatment suggest similar efficacy and safety of CT-P13 SC to CT-P13 IV in RA. The mean serum concentration in all SC cohorts consistently exceeded the threshold of target therapeutic concentration. These results show that the novel SC formulation of CT-P13 may enhance treatment options for use of infliximab biosimilar by providing high consistency in drug exposure. Reference: 1Westhovens et al., Annals of the Rheumatic Disease 2018;77:315. 2Schreiber et al., Gastroenterology 2018;154(6):S-1371. 3Yoo et al., Arthritis Research & Therapy 2016;18:82. Disclosure of Interests: DaeHyun Yoo Grant/research support from: Celltrion, Inc., Consultant for: Celltrion, Inc., Janusz Jaworski Grant/research support from: Celltrion, Inc., Ewa Matyska-Piekarska Grant/research support from: Celltrion, Inc., Svitlana Smiyan Grant/research support from: Celltrion, Inc., Delina Ivanova Grant/research support from: Celltrion, Inc, PPD, Quintiles, Egis Pharmaceuticals, and Pfizer., Agnieszka Zielinska Grant/research support from: Celltrion, Inc., Eve-Kai Raussi Grant/research support from: Celltrion, Inc. and Board of Estonian Society of Rheumatology, Anastas Batalov: None declared, SangJoon Lee Shareholder of: Celltrion, Inc., Employee of: Celltrion, Inc., JeeHye Suh Employee of: Celltrion, Inc., Noori Han Employee of: Celltrion, Inc., Rene Westhovens Grant/research support from: Bristol-Myers Squibb, Consultant for: Celltrion, Galapagos-Gilead